Distinct serum and cerebrospinal fluid cytokine and chemokine profiles in autoantibody-associated demyelinating diseases. Issue 2 (May 2019) - Hofer, Livia S; Mariotto, Sara; Wurth, Sebastian; Ferrari, Sergio; Mancinelli, Chiara R; Delogu, Rachele; Monaco, Salvatore; Gajofatto, Alberto; Schwaiger, Carmen; Rostasy, Kevin; Deisenhammer, Florian; Höftberger, Romana; et al.
Background: Demyelinating diseases of the central nervous system associated with autoantibodies against aquaporin-4 and myelin-oligodendrocyte-glycoprotein are mediated by different immunopathological mechanisms compared to multiple sclerosis. Objective: The purpose of this study was to evaluate serum and cerebrospinal fluid cytokine/chemokine profiles in patients with autoantibodies against aquaporin-4 or autoantibodies against myelin-oligodendrocyte-glycoprotein-associated demyelination compared to multiple sclerosis and autoimmune encephalitis. Methods: Serum and cerebrospinal fluid cytokine/chemokine levels were analysed using Procartaplex Multiplex Immunoassays. First, we analysed a panel of 32 cytokines/chemokines in a discovery group (nine aquaporin-4-antibody seropositive, nine myelin oligodendrocyte glycoprotein-antibody seropositive, eight encephalitis, 10 multiple sclerosis). Significantly dysregulated cytokines/chemokines were validated in a second cohort (11 aquaporin-4-antibody seropositive, 18 myelin oligodendrocyte glycoprotein-antibody seropositive, 18 encephalitis, 33 multiple sclerosis). Results: We found 11 significantly altered cytokines/chemokines in cerebrospinal fluid and serum samples in the discovery group (a proliferation-inducing ligand, fractalkine=CX3CL1, growth-regulated oncogene-α, interleukin-1 receptor antagonist, interleukin-6, interleukin-8=CXCL8, interleukin-10, interleukin-21, interferon-ɣ-induced protein-10=CXCL10, monokine induced by interferon-ɣ=CXCL9, macrophage inflammatory protein-1ß=CCL4). Most of these cytokines/chemokines were up-regulated in autoantibodies against aquaporin-4 or autoantibodies against myelin-oligodendrocyte-glycoprotein positive patients compared to multiple sclerosis. We confirmed these results for cerebrospinal fluid interleukin-6 and serum interleukin-8, growth-regulated oncogene-α, a proliferation-inducing ligand and macrophage inflammatory protein-1β in the validation set. Receiver-operating characteristic analysis revealed increased levels of cerebrospinal fluid interleukin-6, serum interleukin-8 and growth-regulated oncogene-α in most patients with autoantibody-associated neurological diseases. Conclusion: This study suggests that distinctive cerebrospinal fluid and serum cytokine/chemokine profiles are associated with autoantibody-mediated demyelination, but not with multiple sclerosis.